JADWIGA DZIUBIŃSKA AGRICULTURAL EDUCATION CENTRE SCHOOLS IN GOLĄDKOWO MARKETING ACTIVITIES - Krzysztof Nuszkiewicz; Michał Roman (Polityki Europejskie, Finanse i Marketing)
The paper presents the marketing activities of Jadwiga Dziubinska Agricultural Education Centre Schools in Golądkowo. In this regard, attention is drawn to the promotion of the School. With qualified staff of teachers and modern teaching base, the school has achieved many successes that are described in the article. People who start education in Schools in Golądkowo most often choose technical specializations, e.g. an agriculture mechanization technician, a farming technician or an agribusiness technician. Choosing the type of school and their future job, they may take into account various factors, including interests, health and physical condition, knowledge, skills and personality-based capabilities as well as the school authorities and staff’s promotional activities.